Preparation, Characterization and Application of Lubricating Protein Filler for Sustainable Leather Production. Issue 11 (2nd November 2021) - Yorgancioglu, Ali; Onem, Ersin; Basaran, Bahri
ABSTRACT: In this study, collagen hydrolyzate was obtained from bovine shaving wastes of leather production with the alkali hydrolysis reaction. Total amino acid, total carbon and total nitrogen amounts of liquid collagen hydrolyzate (CH) were determined. Fourier-transform infrared spectroscopy (FTIR) characterization of collagen hydrolyzate was performed. Obtained CH was emulsified with hydrogenated castor and amino functional silicone oils to prepare lubricating protein filler (LPF). Particle size and zeta potential of the LPF were analyzed. 10%, 15%, and 20% LPF was used in the retanning/fatliquoring process of chromium tanned bovine leathers. Performance characterizations of leathers treated with LPFs were carried out with tensile strength, tear strength, filling efficiency, light fastness, shrinkage, and denaturation temperature analyses. Moreover, bounded fat content in leather was also determined. Results showed the increased thermal stability, strength performance and good filling effect in leather by application of the prepared LPF. Consequently, LPF had a good potential as natural retanning/fatliquoring agent via achieving reuse of the solid leather wastes and providing satisfactory leather properties and cleaner production by one product itself.